PKM Peningkatkan Keterampilan Mengajar Bertanya Berbasis HOTS Pada Guru TK Yayasan Pendidikan Kristen - Metboki, Yakob; Hambandima, Erny Selfina Nggala; Ludji, Ifoni; Sula, Sisca M. (Universitas Nusantara PGRI Kediri, 2022)
The community service program aims to increase religion school kindergarten teachers’ understanding and skills regarding HOTS-based teaching application. The applied method for implementing the program activities comprises counseling, mentoring, practice and evaluation. The results of the implementation of the innovative program with series of activity stages has resulted kindergarten teachers’ behavior change to implement HOTS-based instruction by utilizing children's storybooks with local content. The results of program account much for further underlying reference of related program and/or research. The community service program is benefited for teachers in conditioning HOTS-based learning. It brings about the implication to Yapenkris Meusine through the partnership program for teachers’ capacity building on pedagogical competence in creating student-centered learning. Another implication goes to teachers’ comprehensive knowledge HOTS-based teaching and learning application to raise students critical and creative thinking. The program is limited on the training regarding HOTS-based questioning skills. Further program may focus on HOTS-based assessment.